Cutaneous wound healing: Current concepts and advances in wound care - Kenneth C Klein; Somes Chandra Guha (Indian Journal of Plastic Surgery)
A non-healing wound is defined as showing no measurable signs of healing for at least 30 consecutive treatments with standard wound care.[1] It is a snapshot of a patient’s total health as well as the ongoing battle between noxious factors and the restoration of optimal macro and micro circulation, oxygenation and nutrition. In practice, standard therapies for non-healing cutaneous wounds include application of appropriate dressings, periodic debridement and eliminating causative factors.[2] The vast majority of wounds would heal by such approach with variable degrees of residual morbidity, disability and even mortality. Globally, beyond the above therapies, newer tools of healing are selectively accessible to caregivers, for various logistical or financial reasons. Our review will focus on the use of hyperbaric oxygen therapy (HBOT), as used at our institution (CAMC), and some other modalities that are relatively accessible to patients. HBOT is a relatively safe and technologically simpler way to deliver care worldwide. However, the expense for including HBOT as standard of care for recognized indications per UHMS(Undersea and Hyperbaric Medical Society) may vary widely from country to country and payment system.[3] In the USA, CMS (Centers for Medicare and Medicaid Services) approved indications for HBOT vary from that of the UHMS for logistical reasons.[1] We shall also briefly look into other newer therapies per current clinical usage and general acceptance by the medical community. Admittedly, there would be other novel tools with variable success in wound healing worldwide, but it would be difficult to include all in this treatise.